1986
DOI: 10.1523/jneurosci.06-07-01857.1986
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting release of 3H-dopamine from perfused carp retina

Abstract: The effects of putative retinal neurotransmitters and several neuropeptides on 3H-dopamine release from isolated perfused carp (Cypriuus curpio) retinas were studied. Of the transmitter candidates tested, only serotonin (S-HT) and the 5-HT agonist tryptamine released "H-dopamine. However, the release evoked by these agents was calcium (Ca*+) independent and not blockable by the 5-HT antagonist methysergide. We also investigated the antagonism of inhibitory inputs as a potential regulatory mechanism for dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…1980). Althought DA release from the vertebrate retina stimulated by both potassium ions (Thomas et al, 1978;Bauer et al, 1980;Frederick et al, 1982), electric current (Dubocovich and Weiner, 1981;Nowak, 1987), and some compounds (O'Connor et al, 1986) has been described in detail by many authors, that evoked by light was studied only in few laboratories. Thus, Kramer (1971) showed that [3H]-DA, perfused pre-retinally, is taken up by the cat's retina, and stimulation by flickering (and not by steady) light increased the rate of release of the [3H]-neurotransmitter (chemical analysis revealed that the major part of the released radioactivity was in the form of DA).…”
Section: Discussionmentioning
confidence: 99%
“…1980). Althought DA release from the vertebrate retina stimulated by both potassium ions (Thomas et al, 1978;Bauer et al, 1980;Frederick et al, 1982), electric current (Dubocovich and Weiner, 1981;Nowak, 1987), and some compounds (O'Connor et al, 1986) has been described in detail by many authors, that evoked by light was studied only in few laboratories. Thus, Kramer (1971) showed that [3H]-DA, perfused pre-retinally, is taken up by the cat's retina, and stimulation by flickering (and not by steady) light increased the rate of release of the [3H]-neurotransmitter (chemical analysis revealed that the major part of the released radioactivity was in the form of DA).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of glutamate antagonists were first examined to determine whether depolarizing or hyperpolarizing bipolar cells control the release of dopamine. In addition, the involvement of GABAergic circuitry was also tested by examining the influence of GABA-related compounds on dopamine release (Marshburn & Iuvone, 1981;O'Connor et al, 1986O'Connor et al, , 1987Piccolino et al, 1982Piccolino et al, , 1987Proll & Morgan, 1983;Teranishi et al, 1984;Ishita et al, 1988). Finally, the agents that increased dopamine efflux were also examined for their effects on retinal levels of cAMP.…”
Section: Introductionmentioning
confidence: 99%
“…Fish were killed by decapitation, enucleated, and each retina was removed by inverting the hemisected eyecup on filter paper and severing the optic nerve. Two retinas from each fish were incubated in the dark in 1 ml of Ringer's solution (80 mM NaCI, 3.5 m M KC1, 22.7 m M NaHCO,, 2.4 mM MgSO,, 2.3 mMCaCI,, 10 mMD-glucose, 10 mMHEPES, 0.1 m M sodium ascorbate, and 15 pM pargyline, pH 7.4) (OConnor et al, 1986) (Marc, 1982). The preparation was continuously bubbled with a mixture of 95% 0, and 5% COz.…”
Section: Preparation Of Retinasmentioning
confidence: 99%